ANALISIS SPASIAL TINGKAT KESTRATEGISAN WILAYAH HUNIAN DAN BISNIS DI KOTA SEMARANG - Hesti Pramudyasti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2020)
This study uses a spatial analysis of geographic information systems to determine the strategic level of a residential area and office business. The spatial analysis used in this research is travel time range analysis based on road network data. Spatial analysis in the form of distance range and travel time were processed using an overlay technique using ArcGIS software. The problem in this research is how the strategic level of residential and business areas in the city of Semarang based on the analysis of the travel time range of public facilities and based on the potential disasters in the city of Semarang. Meanwhile, the aims and objectives of this study are to determine how strategic a residential area (housing) and an office area are based on the range of travel time and the potential for disaster vulnerability using spatial analysis. Based on the calculation results of this study, the highest score is 15 (quite strategic) and the lowest score is 11 (less strategic). The score calculation is based on the number of each weight of the travel time range to the closest public facilities, namely the travel time range to toll gates, train stations, shopping centers, closest health facilities, closest educational facilities, accessibility, surface temperature, and potential risks flood. The strategic level of an area can be determined based on the range of travel time that has taken into account the congestion estimate. Accessibility is one of the most determining factors in determining distance and travel time. The higher the weight score of a place, the more strategic value the place will be.